C++ Programming Assignments. Variants of tasks & Examples of the code: Textbook - Sopronyuk, Tetyana (CreateSpace, 2015)
This textbook is a comprehensive collection of practical tasks designed to develop fundamental and advanced software engineering skills using the C++ programming language. The material focuses on core paradigms of object-oriented programming (OOP), including encapsulation, inheritance, and polymorphism. The book contains 150 structured programming assignments, accompanied by variants of tasks, algorithmic guidelines, and concrete code examples to foster independent problem-solving. It serves as an essential educational resource for computer science students, instructors, and self-taught programmers seeking to master robust software development in C++.
Електронна копія (формат EPUB/PDF) оригінального друкованого видання обсягом 73 сторінки, опублікованого на Amazon KDP (ISBN 978-1515254065). Кількість сторінок у цьому файлі може відрізнятися від друкованої версії через особливості адаптивної верстки цифрового формату
Keywords: Object-oriented programming, C++, Encapsulation, Polymorphism, Inheritance, Code examples, Programming assignments